Global Dynamics of Cryptocurrency Adoption: An Empirical Exploration of Fintech’s Influence on The Evolution of Digital Currencies - Saeed Angorani (PT SOLUSI EDUKASI BERDIKARI, 2024)
This study’s goal is to empirically research the global dynamics of cryptocurrency adoption, with a particular focus on the impact of financial technology (FinTech) breakthroughs on the evolution, acceptability, and integration of digital currencies within the broader financial landscape. This study takes a mixed-methods approach, combining quantitative analysis of global cryptocurrency statistics with qualitative insights from stakeholder interviews. Case studies and a comprehensive literature study help to contextualize FinTech’s impact on the global evolution of digital currencies. This study emphasizes the various drivers driving Bitcoin adoption globally, with FinTech advances at the forefront. Regulatory clarity, technology developments, and changing customer behaviour all influence the trajectory of digital currencies, emphasizing the importance of adaptive methods and collaborative efforts to properly traverse this dynamic field.